Digital Transformation: Identifying Trends in the Covid-Fuelled Brick-To-Click Service Delivery Transition & Establishing Digital Transformation Models – Preliminary Review - Baron, Michael (International Journal of Education Research and Development, 2022)
COVID-19 reached the Australian shores by the end of January 2020 with the disruptive lockdowns commencing in March and continuing on and off till October, 2021. The initial lockdowns have proved to be particularly disruptive to the service industries’ operations as they resulted in dramatic and forced migration of the traditionally brick-and-mortar or hybrid (brick-and-click) operations into the digital space. Being un unplanned move, it has caught many organisations unprepared and without a carefully crafted step-by-step digital transformation plan. In many of the instances, the transition had to be orchestrated literally overnight’. The main objective of this paper is to identify and to examine current state of the digital transformation of the service delivery processes by the means of investigating both literature and the Open Source Data available on the service industries and sectors both locally (in Australia) and internationally. The study is part of the preliminary investigation of the digital transformation ‘’boosters’’ and ‘’blockers’’ with the aim of establishing the Digital Transformation (DT) Framework as well as industry-wide practices for implementation and management of digital transformation programs.